Pengembangan Aplikasi Mobile Berbasis Android untuk Penilaian Kinerja Guru di MTs Baiturrohim Menggunakan Metode Multi-Objective Optimization on the Basis of Ratio Analysis - Afrizal Fanani; Iftitaahul Mufarrihah (Universitas Methodist Indonesia, 2026)
This study integrates an Android-based mobile application system for teacher performance evaluation with the development of the MOORA method. This system is designed to transform conventional evaluation mechanisms into a digital platform that is more objective, efficient, and transparent. The Agile model was used for its development. The MOORA algorithm is implemented to process four main criteria of teacher competence pedagogical, personal, social, and professional which are broken down into 78 performance indicators. Test results show that the system successfully identified a Pearson correlation of 0.9999, which falls into the very strong category.